Characterization of hydrocoptisonine metabolites in human liver microsomes using a high-resolution quadrupole-orbitrap mass spectrometer. (1st December 2020) - Choi, Su Min; Kim, Younah; Lee, Jaeick; Kim, Ju-Hyun; Lee, Taeho; Min, Byung Sun; Kim, Jeong Ah; Lee, Sangkyu
Abstract: Hydrocoptisonine is a new compound that has been isolated from the rhizomes of Coptis chinensis, which belongs to the Ranunculaceae family of Chinese medicines. Although studies on C. chinensis have been reported, the metabolic pathway of hydrocoptisonine in human liver microsomes (HLMs) remains unelucidated. We identified 13 metabolites in HLMs, including six Phase I metabolites and seven glucuronide conjugates, using a high-resolution quadrupole-orbitrap mass spectrometer. The major metabolic pathway was the O -demethylation and mono-hydroxylation of hydrocoptisonine in HLMs. Notably, M3 metabolite was O -demethylated in dioxolane structures (cyclohexa-3, 5-diene-1, 2-dione), which was mediated by cytochrome P450 1A2. The locations of hydroxylation and hydroxyl-glucuronidation were identified by analyzing the signature fragments generated as a result of tandem mass spectrometry, indicating hydroxylation at an aliphatic chain or aromatic ring. We determined whether the hydroxylation and glucuronidation occurred in an aromatic moiety (M5 and M12) or an aliphatic moiety (M6 and M13), respectively, based on signature fragments of the metabolites.